Lightweight high-strength plastic material and method of manufacture

CN122941087APending Publication Date: 2026-10-20ANHUI HUIYAN TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610914811.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

现有技术对于凹凸棒土的功能改性以增强聚丙烯树脂的研究仍有可探索空间

Benefits of technology

[0034]利用凹凸棒土棒晶作为纳米纤维骨架,在PP基体中形成增强网络,而改性凹凸棒土在凹凸棒土棒晶的端部选择性接枝成核剂,诱导PP分子链沿棒晶轴向取向结晶,形成横穿晶结构,改善界面应力传递,冲击强度保持率优于传统填料体系,在保持聚丙烯树脂轻质特性的基础上,提高了弯曲模量和耐热性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This application discloses a lightweight, high-strength plastic material and its preparation method. The lightweight, high-strength plastic material includes polypropylene resin and modified attapulgite; for every 100 parts by weight of polypropylene resin, the amount of modified attapulgite is 2-10 parts; wherein, the modified attapulgite is attapulgite rod crystals with end-selectively grafted nucleating agents. Using attapulgite rod crystals as a nanofiber framework, a reinforcing network is formed in the PP matrix. The modified attapulgite selectively grafts nucleating agents at the ends of the attapulgite rod crystals, inducing the PP molecular chains to crystallize along the rod crystal axis, forming a transverse crystal structure, improving interfacial stress transmission, and exhibiting a better impact strength retention rate than traditional filler systems. While maintaining the lightweight characteristics of polypropylene resin, it also improves the flexural modulus and heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polymer materials technology, and in particular to a lightweight, high-strength plastic material and its preparation method. Background Technology

[0002] Polypropylene (PP), as a general-purpose thermoplastic, has advantages such as low density, good chemical stability, and easy processing, and is widely used in automobiles, home appliances, packaging and other fields. However, polypropylene has defects such as large molding shrinkage, poor low-temperature toughness, and insufficient rigidity.

[0003] Currently, methods to improve the performance of polypropylene include adding inorganic fillers to improve rigidity and heat resistance, and adding elastomers to improve toughness. However, adding inorganic fillers often leads to a decrease in impact toughness, while adding elastomers will also sacrifice rigidity and heat resistance to some extent.

[0004] Attapulgite (ATP) is a hydrous magnesium-aluminate silicate clay mineral with a nanoscale rod-shaped crystal structure. It is widely used in functional fillers to improve performance.

[0005] The prior art CN122127697A discloses a polypropylene composition and its preparation method and application. By introducing long-chain branched polypropylene and modified rod-shaped particles with a core-shell structure into the polypropylene resin of the glass fiber reinforced system, the synergistic effect of the two with the matrix resin can overcome the problem of low strength in the weld line area of ​​existing products, while also ensuring high dimensional stability of the product during processing and reducing warpage. The modified rod-shaped particles can be composed of attapulgite, and the modified rod-shaped particles with a core-shell structure can act as a nucleating agent for polypropylene resin to a certain extent, refining the spherulite size.

[0006] In a prior art patent CN121758862A, a low-odor reinforced polypropylene composite material and its preparation method are disclosed, a composite adsorbent is added to the polypropylene resin. The composite adsorbent is composed of an inorganic carrier with adsorption function and an organic component with adsorption or catalytic conversion function. The inorganic carrier is attapulgite, which, due to its extremely large specific surface area and nanoscale micropores, is primarily responsible for adsorbing high molecular weight VOCs.

[0007] It is evident that modifying attapulgite based on its different performance characteristics and applying it to polypropylene resin can produce various technical effects. There is still room for further exploration in current technologies for the functional modification of attapulgite to enhance polypropylene resin. Summary of the Invention

[0008] In order to solve at least one of the above-mentioned technical problems and to develop a polypropylene composite material with high rigidity, good toughness and excellent crystallinity, this application provides a lightweight high-strength plastic material and a preparation method thereof.

[0009] On the one hand, this application provides a lightweight and high-strength plastic material, comprising: polypropylene resin and modified attapulgite; for every 100 parts by weight of polypropylene resin, the amount of modified attapulgite is 2 to 10 parts.

[0010] The modified attapulgite is attapulgite rod crystals with end-selective grafting nucleating agents.

[0011] By adopting the above technical solution, attapulgite rod crystals are used as nanofiber skeletons to form a reinforcing network in the PP matrix. Modified attapulgite selectively grafts nucleating agents at the ends of the attapulgite rod crystals, inducing PP molecular chains to crystallize along the rod crystal axis to form a transverse crystal structure, which improves the interfacial stress transmission and has a better impact strength retention rate than traditional filler systems. While maintaining the lightweight characteristics of polypropylene resin, the flexural modulus and heat resistance are improved.

[0012] Optionally, the length of the attapulgite rod crystal is 1 to 3 μm, and the aspect ratio is not less than 20:1.

[0013] By adopting the above technical solution, the length of the attapulgite rod crystals is selected to be 1-3 μm to match the size of the PP molecular chain, which is conducive to the transfer of interfacial stress. The aspect ratio is the threshold for forming effective fiber reinforcement. Below this value, the reinforcement effect is significantly reduced. The high aspect ratio ensures that the transverse crystal structure grows fully along the rod crystal axis. In addition, the high aspect ratio combined with the injection molding orientation advantage can enable the composite material to obtain the maximum reinforcement effect in the flow direction, and the flexural modulus and tensile strength reach the optimal balance point.

[0014] Optionally, the cation exchange capacity of the attapulgite rod crystals does not exceed 30 meq / 100g, and the specific surface area is 150-210 m² / g.

[0015] By adopting the above technical solution, the low cation exchange capacity ensures the end selectivity of the grafting reaction, avoids the non-specific grafting of nucleating agents to the side, and the moderate specific surface area provides sufficient grafting sites while avoiding the structural damage associated with excessively high specific surface area.

[0016] Optionally, the degree of dissociation of the rod-shaped crystal bundles of the attapulgite is not less than 90%.

[0017] By adopting the above technical solution, a sufficient proportion of single rod crystals is ensured, so that the ends of each rod crystal are fully exposed, improving the accessibility of end grafting and avoiding the problem of hidden ends caused by the aggregation of rod crystal bundles; at the same time, the dispersion uniformity is improved, micron-sized agglomerates are reduced as stress concentration points, the interface area is increased, and the stress transfer efficiency is improved.

[0018] Optionally, the polypropylene resin is a highly crystalline homopolymer polypropylene with a melt index of 5–15 g / 10 min.

[0019] By adopting the above technical solution, high crystallinity PP is more sensitive to nucleating agents, transverse crystals are easier to form and grow more densely; the melt index of 5-15 g / 10min ensures the flowability matching when blended with attapulgite, and ensures that the attapulgite is highly oriented along the flow direction during injection molding. Too high an index will make processing difficult, while too low an index will lead to insufficient matrix strength.

[0020] Optionally, the nucleating agent is an aromatic amide β-nucleating agent.

[0021] By adopting the above technical solution, β nucleating agents are used to induce PP to form β crystals, which have large crystal thickness and loose arrangement, which is conducive to the formation of transverse crystal structure; while aromatic amide β nucleating agents have specific molecular structures and can be stably connected with attapulgite end groups through amide bonds, thereby improving the impact toughness and heat distortion temperature of plastics.

[0022] Secondly, this application provides a method for preparing the above-mentioned lightweight high-strength plastic material, including:

[0023] Activated attapulgite is obtained by purifying and activating the end groups of attapulgite rod crystals.

[0024] The activated attapulgite was dispersed in a solvent, a coupling agent was added, and the mixture was refluxed at 100–110°C for 4–6 hours under nitrogen protection. After washing and drying, the coupling agent-modified attapulgite was obtained.

[0025] The coupling agent-modified attapulgite, nucleating agent, and condensing agent are added to a solvent to carry out a grafting reaction, and the reaction product is extracted and purified by a Soxhlet extractor to obtain modified attapulgite.

[0026] The modified attapulgite clay and polypropylene resin are mixed in a certain proportion, and then melt-blended and extruded in a twin-screw extruder to obtain a lightweight, high-strength plastic material.

[0027] By adopting the above technical solution, a four-step method combined with Soxhlet extraction was used to achieve end-selective chemical grafting and to stably prepare PP / ATP composite materials with excellent performance.

[0028] Optionally, the purification process includes: preparing an aqueous suspension of attapulgite rod crystals, followed by high-speed stirring, static sedimentation, centrifugation, drying, and sieving to obtain purified attapulgite rod crystals;

[0029] The end-group activation treatment includes: adding purified attapulgite rod crystals to a 0.5-2.0M hydrochloric acid solution, refluxing at 60-90°C for 1-4 hours, washing until neutral and drying to obtain activated attapulgite.

[0030] By adopting the above technical solution, the density of end-group silanol groups in activated attapulgite soil is increased by more than 50%, while maintaining the integrity of the crystal structure.

[0031] Optionally, before adding the coupling agent-modified attapulgite, nucleating agent, and condensing agent to the solvent for grafting reaction, the method further includes: subjecting the activated attapulgite to flow field-assisted dispersion treatment, wherein the flow field-assisted dispersion treatment is ultrasonic dispersion treatment for 20 to 60 min under the conditions of frequency 20 to 40 kHz and power density 50 to 200 W / L.

[0032] By adopting the above technical solutions, the degree of dissociation of attapulgite rod crystal bundles can be improved. The ultrasonic field can induce the directional alignment of the rod crystals, with the ends preferentially facing the reaction medium, thereby improving the selectivity of end grafting.

[0033] In summary, the present invention has at least one of the following beneficial technical effects:

[0034] Attapulgite rod crystals are used as a nanofiber skeleton to form a reinforcing network in the PP matrix. Modified attapulgite selectively grafts nucleating agents at the ends of the attapulgite rod crystals, inducing PP molecular chains to crystallize along the rod crystal axis, forming a transverse crystal structure, which improves interfacial stress transmission. The impact strength retention rate is better than that of traditional filler systems. While maintaining the lightweight characteristics of polypropylene resin, the flexural modulus and heat resistance are improved. Detailed Implementation

[0035] The present application will be further described in detail below with reference to the embodiments.

[0036] This application designs a lightweight, high-strength plastic material, comprising: polypropylene resin and modified attapulgite; for every 100 parts by weight of polypropylene resin, the amount of modified attapulgite is 2 to 10 parts.

[0037] The modified attapulgite is attapulgite rod crystals with end-selective grafting nucleating agents.

[0038] In this invention, other components, such as antioxidants, light stabilizers, and POE toughening agents, can be added to the lightweight, high-strength plastic material, selectively according to specific application requirements.

[0039] The lightweight, high-strength plastic material of this application is prepared by the following method, including the following steps:

[0040] Activated attapulgite is obtained by purifying and activating the end groups of attapulgite rod crystals.

[0041] The activated attapulgite was dispersed in a solvent, a coupling agent was added, and the mixture was refluxed at 100–110°C for 4–6 hours under nitrogen protection. After washing and drying, the coupling agent-modified attapulgite was obtained.

[0042] The coupling agent-modified attapulgite, nucleating agent, and condensing agent are added to a solvent to carry out a grafting reaction, and the reaction product is extracted and purified by a Soxhlet extractor to obtain modified attapulgite.

[0043] The modified attapulgite clay and polypropylene resin are mixed in a certain proportion, and then melt-blended and extruded in a twin-screw extruder to obtain a lightweight, high-strength plastic material. Specific Implementation

[0044] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments and comparative examples. The purpose of this description is to provide a detailed understanding of the invention, not to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention. Unless otherwise specified, the experimental reagents and instruments involved in the implementation of this invention are commonly used reagents and instruments.

[0045] In the following embodiments and comparative examples of the present invention, all raw materials and reagents were obtained through commercial procurement.

[0046] Example 1

[0047] Polypropylene resin is used as the matrix, with the addition of modified attapulgite, antioxidants and calcium stearate.

[0048] The antioxidant is a compound of hindered phenolic antioxidant Irganox 1010 and phosphite antioxidant Irgafos 168 in a mass ratio of 1:2.

[0049] The polypropylene resin is HP500N, a highly crystalline homopolymer polypropylene resin, with a melt flow rate of 12 g / 10 min at 230℃ and 2.16 kg load, according to ISO 1133-2011.

[0050] Preparation method of modified attapulgite

[0051] (I) Purification and end-group activation treatment of attapulgite soil

[0052] Attapulgite soil was prepared into a 5 wt% aqueous suspension, stirred at 8000 rpm for 30 min, allowed to settle, and the supernatant was collected and centrifuged at 4000 rpm for 15 min, repeated 3 times. The precipitate was collected, dried under vacuum at 60℃, and passed through a 200-mesh sieve to obtain purified attapulgite soil.

[0053] The purified attapulgite was added to 0.8 M hydrochloric acid solution at a solid-liquid ratio of 1:20, refluxed and stirred at 80°C for 2 hours, washed with deionized water until neutral, washed twice with anhydrous ethanol, and dried under vacuum at 80°C to obtain activated attapulgite.

[0054] (ii) Selective grafting of end groups

[0055] Activated attapulgite was dispersed in anhydrous toluene at a solid-liquid ratio of 1:15 and ultrasonically dispersed for 30 min at a frequency of 25 kHz and a power density of 100 W / L. 15% (by weight of the activated attapulgite) of coupling agent KH550 was added, and the mixture was refluxed at 105 °C for 5 h under nitrogen protection. After the reaction, the mixture was centrifuged, washed three times each with toluene and anhydrous ethanol, and dried under vacuum at 60 °C to obtain grafted attapulgite.

[0056] Grafted attapulgite was dispersed in anhydrous DMF at a solid-liquid ratio of 1:20. 25% (by weight of the grafted attapulgite) of TMB-5 and a condensing agent (EDC·HCl and NHS in a molar ratio of 1:1.2) were added. The reaction was carried out at room temperature for 24 hours under nitrogen protection. After the reaction, the mixture was centrifuged, thoroughly washed with DMF and anhydrous ethanol, and then Soxhlet extracted with acetone for 24 hours. The mixture was then vacuum dried at 60°C to obtain the modified attapulgite.

[0057] The rods of activated attapulgite in the above method have an average length of 2 μm, an average aspect ratio of 20:1, an average cation exchange capacity of 13 meq / 100g, an average specific surface area of ​​180 m² / g, and a rod bundle dissociation degree of 92%.

[0058] Preparation method of polypropylene composite material

[0059] Modified attapulgite clay, polypropylene resin, antioxidant, and calcium stearate lubricant were premixed in a high-speed mixer for 3 minutes according to the formula ratio, and then added to a twin-screw extruder for melt extrusion granulation. The temperatures of each zone of the twin-screw extruder were set as follows: Zone 1 180℃, Zone 2 190℃, Zone 3 200℃, Zone 4 200℃, Zone 5 200℃, Zone 6 200℃, Zone 7 200℃, Zone 8 200℃, Zone 9 200℃, and Zone 10 200℃. The screw speed was 250 rpm, and the screw length-to-diameter ratio was 40:1.

[0060] After water cooling and granulation, the extruded granules are dried in a vacuum drying oven at 80℃ for 4 hours. The dried granules are then injection molded into standard test specimens at a mold temperature of 70℃, and the specimens are annealed in a vacuum oven at 130℃ for 2 hours.

[0061] Comparative Example 1

[0062] Compared to Example 1, only polypropylene resin was used.

[0063] Preparation method of polypropylene composite material

[0064] Polypropylene resin was added to a twin-screw extruder for melt extrusion granulation. The temperatures of each zone of the twin-screw extruder were set as follows: Zone 1 180℃, Zone 2 190℃, Zone 3 200℃, Zone 4 200℃, Zone 5 200℃, Zone 6 200℃, Zone 7 200℃, Zone 8 200℃, Zone 9 200℃, and Zone 10 200℃. The screw speed was 250 rpm, and the screw length-to-diameter ratio was 40:1.

[0065] After water cooling and granulation, the extruded granules are dried in a vacuum drying oven at 80℃ for 4 hours. The dried granules are then injection molded into standard test specimens at a mold temperature of 70℃, and the specimens are annealed in a vacuum oven at 130℃ for 2 hours.

[0066] Comparative Example 2

[0067] Compared to Example 1, polypropylene resin was used as the matrix, and nucleating agents, antioxidants and calcium stearate were added.

[0068] Preparation method of polypropylene composite material

[0069] The nucleating agent, polypropylene resin, antioxidant, and lubricant were premixed in a high-speed mixer for 3 minutes according to the formula ratio, and then added to a twin-screw extruder for melt extrusion granulation. The temperatures of each zone of the twin-screw extruder were set as follows: Zone 1 180℃, Zone 2 190℃, Zone 3 200℃, Zone 4 200℃, Zone 5 200℃, Zone 6 200℃, Zone 7 200℃, Zone 8 200℃, Zone 9 200℃, and Zone 10 200℃. The screw speed was 250 rpm, and the screw length-to-diameter ratio was 40:1.

[0070] After water cooling and granulation, the extruded granules are dried in a vacuum drying oven at 80℃ for 4 hours. The dried granules are then injection molded into standard test specimens at a mold temperature of 70℃, and the specimens are annealed in a vacuum oven at 130℃ for 2 hours.

[0071] Comparative Example 3

[0072] Compared to Example 1, this example uses polypropylene resin as the matrix and adds grafted attapulgite, antioxidants, and calcium stearate.

[0073] Preparation method of grafted attapulgite soil

[0074] (I) Purification and end-group activation treatment of attapulgite soil

[0075] Attapulgite soil was prepared into a 5 wt% aqueous suspension, stirred at 8000 rpm for 30 min, allowed to settle, and the supernatant was collected and centrifuged at 4000 rpm for 15 min, repeated 3 times. The precipitate was collected, dried under vacuum at 60℃, and passed through a 200-mesh sieve to obtain purified attapulgite soil.

[0076] The purified attapulgite was added to 0.8 M hydrochloric acid solution at a solid-liquid ratio of 1:20, refluxed and stirred at 80°C for 2 hours, washed with deionized water until neutral, washed twice with anhydrous ethanol, and dried under vacuum at 80°C to obtain activated attapulgite.

[0077] (ii) Selective grafting of end groups

[0078] Activated attapulgite was dispersed in anhydrous toluene at a solid-liquid ratio of 1:15 and ultrasonically dispersed for 30 min at a frequency of 25 kHz and a power density of 100 W / L. 15% (by weight of the activated attapulgite) of KH550 was added, and the mixture was refluxed at 105 °C for 5 h under nitrogen protection. After the reaction, the mixture was centrifuged, washed three times each with toluene and anhydrous ethanol, and dried under vacuum at 60 °C to obtain grafted attapulgite.

[0079] Preparation method of polypropylene composite material

[0080] Grafted attapulgite clay, polypropylene resin, antioxidant, and lubricant were premixed in a high-speed mixer for 3 minutes according to the formula ratio, and then added to a twin-screw extruder for melt extrusion granulation. The temperatures of each zone of the twin-screw extruder were set as follows: Zone 1 180℃, Zone 2 190℃, Zone 3 200℃, Zone 4 200℃, Zone 5 200℃, Zone 6 200℃, Zone 7 200℃, Zone 8 200℃, Zone 9 200℃, and Zone 10 200℃. The screw speed was 250 rpm, and the screw length-to-diameter ratio was 40:1.

[0081] After water cooling and granulation, the extruded granules are dried in a vacuum drying oven at 80℃ for 4 hours. The dried granules are then injection molded into standard test specimens at a mold temperature of 70℃, and the specimens are annealed in a vacuum oven at 130℃ for 2 hours.

[0082] Comparative Example 4

[0083] Compared with Example 1, polypropylene resin was used as the matrix, and grafted attapulgite, nucleating agent, antioxidant and calcium stearate were added.

[0084] Preparation method of grafted attapulgite soil

[0085] (I) Purification and end-group activation treatment of attapulgite soil

[0086] Attapulgite soil was prepared into a 5 wt% aqueous suspension, stirred at 8000 rpm for 30 min, allowed to settle, and the supernatant was collected and centrifuged at 4000 rpm for 15 min, repeated 3 times. The precipitate was collected, dried under vacuum at 60℃, and passed through a 200-mesh sieve to obtain purified attapulgite soil.

[0087] The purified attapulgite was added to 0.8 M hydrochloric acid solution at a solid-liquid ratio of 1:20, refluxed and stirred at 80°C for 2 hours, washed with deionized water until neutral, washed twice with anhydrous ethanol, and dried under vacuum at 80°C to obtain activated attapulgite.

[0088] (ii) Selective grafting of end groups

[0089] Activated attapulgite was dispersed in anhydrous toluene at a solid-liquid ratio of 1:15 and ultrasonically dispersed for 30 min at a frequency of 25 kHz and a power density of 100 W / L. 15% (by weight of the activated attapulgite) of KH550 was added, and the mixture was refluxed at 105 °C for 5 h under nitrogen protection. After the reaction, the mixture was centrifuged, washed three times each with toluene and anhydrous ethanol, and dried under vacuum at 60 °C to obtain grafted attapulgite.

[0090] Preparation method of polypropylene composite material

[0091] Grafted attapulgite, nucleating agent, polypropylene resin, antioxidant, and lubricant were premixed in a high-speed mixer for 3 minutes according to the formula ratio, and then added to a twin-screw extruder for melt extrusion granulation. The temperatures of each zone of the twin-screw extruder were set as follows: Zone 1 180℃, Zone 2 190℃, Zone 3 200℃, Zone 4 200℃, Zone 5 200℃, Zone 6 200℃, Zone 7 200℃, Zone 8 200℃, Zone 9 200℃, and Zone 10 200℃. The screw speed was 250 rpm, and the screw length-to-diameter ratio was 40:1.

[0092] After water cooling and granulation, the extruded granules are dried in a vacuum drying oven at 80℃ for 4 hours. The dried granules are then injection molded into standard test specimens at a mold temperature of 70℃, and the specimens are annealed in a vacuum oven at 130℃ for 2 hours.

[0093] The specific formulations and testing performance of Example 1 and Comparative Examples 1 to 4 are shown in Table 1.

[0094] Table 1:

[0095] Components / Performance Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Polypropylene resin (parts) 100 100 100 100 100 β-ATP (parts) 5 0 0 0 0 KH550-ATP (per serving) 0 0 0 5 5 TMB-5 (serves) 0 0 0.15 0 0.15 Antioxidant (parts) 0.3 0.3 0.3 0.3 0.3 Calcium stearate (parts) 0.2 0.2 0.2 0.2 0.2 Flexural modulus (MPa) 2510 1350 1520 1850 1920 Impact strength (kJ / m², 23℃) 5.8 3.2 3.8 3.5 4.2 Impact strength (kJ / m², -30℃) 3.1 1.8 2 2 2.5 Heat distortion temperature (°C) 132 105 112 118 121 β crystal content (K value) 0.78 0.05 0.72 0.08 0.52 Transverse crystal structure (POM) Clear and complete none none part part

[0096] In Table 1, the amount of polypropylene resin used is 20 kg, and other corresponding components are added according to the weight ratio.

[0097] β-ATP refers to modified attapulgite, KH550-ATP refers to grafted attapulgite, and TMB-5 refers to nucleating agent.

[0098] In Example 1, the mass of the nucleating agent anchored on β-ATP was measured to be 0.15 g.

[0099] Referring to Table 1, the flexural modulus, impact strength, heat distortion temperature, and β-crystal content of Example 1 are significantly better than those of the comparative examples. Comparative Example 1, with pure PP, has the worst performance; Comparative Example 2, although it has added a nucleating agent, lacks the reinforcement of the attapulgite skeleton, resulting in limited improvement in rigidity; Comparative Example 3, with only KH550-ATP added and no nucleating agent, has a low β-crystal content and no significant improvement in toughness; Comparative Example 4, a physical blend of KH550-ATP and TMB-5, has a certain β-crystal content, but it is far lower than that of Example 1, and its flexural modulus and impact strength are also lower than those of Example 1. This indicates that the end-selective chemical grafting structure in this invention is the key to achieving excellent comprehensive performance.

[0100] Example 2

[0101] This embodiment modifies the parameters of the attapulgite rod crystals based on Comparative Example 1:

[0102] The average length is 1 μm and the average aspect ratio is 55:1.

[0103] Example 3

[0104] This embodiment modifies the parameters of the attapulgite rod crystals based on Comparative Example 1:

[0105] The average length is 3 μm and the average aspect ratio is 100:1.

[0106] Comparative Example 5

[0107] This embodiment modifies the parameters of the attapulgite rod crystals based on Comparative Example 1:

[0108] The average length is 0.8 μm and the average aspect ratio is 29:1.

[0109] Comparative Example 6

[0110] This embodiment modifies the parameters of the attapulgite rod crystals based on Comparative Example 1:

[0111] The average length is 4.5 μm and the average aspect ratio is 150:1.

[0112] Comparative Example 7

[0113] This embodiment modifies the parameters of the attapulgite rod crystals based on Comparative Example 1:

[0114] The average length is 2 μm and the average aspect ratio is 10:1.

[0115] The detection performance of Examples 2 and 3 and Comparative Examples 5 to 7 is shown in Table 2.

[0116] Table 2:

[0117] Components / Performance Example 2 Example 3 Comparative Example 5 Comparative Example 6 Comparative Example 7 Average length of attapulgite soil (μm) 1 3 0.8 4.5 2 Aspect Ratio 55:1 100:1 29:1 150:1 10:1 Flexural modulus (MPa) 2560 2610 2050 2150 1680 Impact strength (kJ / m², 23℃) 6 5.9 4.5 4 3.6 Impact strength (kJ / m², -30℃) 3.3 3.2 2.4 2.1 1.9 Heat distortion temperature (°C, 0.45 MPa) 133 135 119 123 108 β crystal content (K value) 0.81 0.79 0.58 0.65 0.42 Transverse crystal structure (POM) Clear and complete Clear and complete part Partial (broken rod) Not obvious Appearance defects none none none Appearance defects none

[0118] According to Table 2, the flexural modulus of Examples 1 to 3 are all above 2510 MPa, the impact strength (23℃) is all above 5.8 kJ / m², the heat distortion temperature is all above 132℃, the β crystal content is all above 0.78, and a clear and complete transverse crystal structure can be observed under a polarizing microscope.

[0119] Although Comparative Example 5 has an aspect ratio of ≥20:1, its length is less than 1μm, resulting in a significant reduction in fiber reinforcement effect. Its flexural modulus is only 2050 MPa, its impact strength is 4.5 kJ / m², and its transverse crystal structure is incomplete.

[0120] Comparative Example 6 suffered from excessively long crystal rods, resulting in numerous rod breakages during processing. This led to a flexural modulus of only 2150 MPa, an impact strength of 4.0 kJ / m², and surface defects such as floating fibers appearing on the injection-molded product.

[0121] Comparative Example 7 has an aspect ratio of less than 20:1, which makes it impossible to form an effective fiber reinforcement network. Its flexural modulus is only 1680 MPa, its impact strength is only 3.6 kJ / m², its β crystal content is only 0.42, and no obvious transverse crystal structure is observed under a polarizing microscope. Its performance is close to that of pure PP.

[0122] The above results indicate that when the length of the attapulgite rod crystals is 1–3 μm and the aspect ratio is ≥20:1, the fiber reinforcement effect of the attapulgite rod crystals can be fully utilized and the transverse crystal structure can be induced, thereby obtaining excellent comprehensive performance.

[0123] Example 4

[0124] This embodiment modifies the activation conditions of Comparative Example 1 to: 0.5 M HCl, 70°C, 1.5 h;

[0125] Parameters of attapulgite rod crystals:

[0126] The average cation exchange capacity is 30 meq / 100g, and the average specific surface area is 150 m² / g.

[0127] Example 5

[0128] This embodiment modifies the activation conditions of Comparative Example 1 to: 0.8 M HCl, 80°C, 2.5 h;

[0129] Parameters of attapulgite rod crystals:

[0130] The average cation exchange capacity is 18 meq / 100g, and the average specific surface area is 210 m² / g.

[0131] Comparative Example 8

[0132] This embodiment modifies the activation conditions of Comparative Example 1 to: 1.5 M HCl, 90°C, 3 h;

[0133] Parameters of attapulgite rod crystals:

[0134] The average cation exchange capacity is 35 meq / 100g, and the average specific surface area is 178 m² / g.

[0135] Comparative Example 9

[0136] This embodiment modifies the activation conditions of Comparative Example 1 to: 0.2 M HCl, 60°C, 1 h;

[0137] Parameters of attapulgite rod crystals:

[0138] The average cation exchange capacity is 18 meq / 100g, and the average specific surface area is 140 m² / g.

[0139] Comparative Example 10

[0140] This embodiment modifies the activation conditions of Comparative Example 1 to: 2.0 M HCl, 90°C, 4 h;

[0141] Parameters of attapulgite rod crystals:

[0142] The average cation exchange capacity is 18 meq / 100g, and the average specific surface area is 220 m² / g.

[0143] The detection performance of Examples 4 and 5 and Comparative Examples 8 to 10 is shown in Table 3.

[0144] Table 3:

[0145] Components / Performance Example 4 Example 5 Comparative Example 8 Comparative Example 9 Comparative Example 10 CEC (meq / 100g) 30 18 35 18 18 Specific surface area (m² / g) 150 210 178 140 220 XRD crystal plane peak retention 0.88 0.9 0.62 0.96 0.58 Flexural modulus (MPa) 2410 2480 1980 1950 2010 Impact strength (kJ / m², 23℃) 5.5 5.7 4.2 4 4.3 Impact strength (kJ / m², -30℃) 2.9 3.1 2.2 2.1 2.3 Heat distortion temperature (°C, 0.45 MPa) 128 130 116 114 117 β crystal content (K value) 0.74 0.77 0.55 0.52 0.56 Transverse crystal structure (POM) whole Clear and complete part Not obvious Partial (uneven structure) Appearance defects none none none There is a reunion none

[0146] According to Table 3, the flexural modulus of Examples 4 and 5 are 2410 MPa and 2480 MPa, respectively; the impact strength is 5.5 kJ / m² and 5.7 kJ / m², respectively; and the heat distortion temperature is 128℃ and 130℃, respectively. All of these are significantly better than pure PP and the comparative examples.

[0147] Comparative Example 8, due to CEC exceeding 30, had an XRD crystal plane peak retention rate of only 62%, with obvious crystal structure damage. Agglomeration was observed in the cross-section SEM, with a flexural modulus of only 1980 MPa and an impact strength of only 4.2 kJ / m².

[0148] Comparative Example 9 has a specific surface area of ​​less than 150, insufficient end-group active sites, low grafting rate, and indistinct transverse crystal structure. Its flexural modulus is only 1950 MPa and its impact strength is only 4.0 kJ / m².

[0149] Comparative Example 10, with a specific surface area higher than 210, had an XRD crystal plane peak retention rate of only 58%. Overactivation led to severe damage to the crystal structure. Although the CEC was still 18, the grafting rate was low, the structure was uneven, the flexural modulus was only 2010 MPa, and the impact strength was only 4.3 kJ / m².

[0150] The above results indicate that only when the cation exchange capacity of attapulgite does not exceed 30 meq / 100g and the specific surface area is 150–210 m² / g can the integrity of the crystal structure and the sufficiency of end-group active sites be basically guaranteed, thereby obtaining the ideal grafting rate and the comprehensive performance of the composite material.

[0151] Example 6

[0152] This embodiment modifies the ultrasonic dispersion conditions based on Comparative Example 1: 25 kHz, 100 W / L, 25 min; and obtains attapulgite rod crystals with a dissociation degree of 90%.

[0153] Comparative Example 11

[0154] This embodiment modifies the ultrasonic dispersion conditions based on Comparative Example 1: 20 kHz, 80 W / L, 30 min; and obtains attapulgite rod crystals with a dissociation degree of 87%.

[0155] The detection performance of Example 6 and Comparative Example 11 is shown in Table 4.

[0156] Table 4:

[0157] Components / Performance Example 6 Comparative Example 11 Flexural modulus (MPa) 2480 2080 Impact strength (kJ / m², 23℃) 5.6 4.3 Impact strength (kJ / m², -30℃) 3 2.3 Heat distortion temperature (°C, 0.45 MPa) 129 122 β crystal content (K value) 0.76 0.61 Transverse crystal structure (POM) whole part Appearance defects none none

[0158] Referring to Table 3, Example 6 has a flexural modulus of 2480 MPa, an impact strength of 5.6 kJ / m², a heat distortion temperature of 129°C, and a β-crystal content of 0.76. Comparative Example 11, due to its dissociation degree being below 90%, has a low grafting rate, a flexural modulus of only 2080 MPa, an impact strength of only 4.3 kJ / m², a heat distortion temperature of only 122°C, and a β-crystal content of only 0.61, with an incomplete transverse crystal structure. It is noteworthy that although the dissociation degree of Comparative Example 11 differs from that of Example 6 by only 3 percentage points, Example 6 has a flexural modulus 400 MPa higher, an impact strength 1.3 kJ / m² higher, and a β-crystal content 0.15 higher than Comparative Example 11. This indicates that 90% is a critical threshold: when the dissociation degree is below 90%, the undissociated rod-shaped crystal bundles have a significant negative impact on performance; when the dissociation degree reaches above 90%, the proportion of single rod-shaped crystals is sufficiently high, the ends are fully exposed, and the grafting efficiency and composite material properties experience a leap.

[0159] The results show that a bar crystal bundle dissociation degree of ≥90% is an important condition for ensuring full exposure of the attapulgite ends, achieving efficient grafting, and forming a complete transverse crystal structure.

[0160] Example 7

[0161] This embodiment modifies the polypropylene resin parameters based on Comparative Example 1: MFI = 5 g / 10min.

[0162] Example 8

[0163] This embodiment modifies the polypropylene resin parameters based on Comparative Example 1: MFI = 15 g / 10min.

[0164] Comparative Example 12

[0165] This embodiment modifies the polypropylene resin parameters based on Comparative Example 1: MFI = 2.5 g / 10min.

[0166] Comparative Example 13

[0167] This embodiment modifies the polypropylene resin parameters based on Comparative Example 1: MFI = 20 g / 10 min.

[0168] Comparative Example 14

[0169] This embodiment modifies the polypropylene resin parameters based on Comparative Example 1: the homopolymer polypropylene resin is replaced with copolymer polypropylene resin K8003, and MFI=8g / 10min.

[0170] The detection performance of Examples 7, 8 and Comparative Examples 12 to 14 is shown in Table 5.

[0171] Table 5:

[0172] Components / Performance Example 7 Example 8 Comparative Example 12 Comparative Example 13 Comparative Example 14 Flexural modulus (MPa) 2480 2510 2180 2010 2250 Impact strength (kJ / m², 23℃) 5.7 5.8 5.2 4.5 4.8 Impact strength (kJ / m², -30℃) 3 3.1 2.7 2.3 2.5 Heat distortion temperature (°C, 0.45 MPa) 129 131 126 118 124 β crystal content (K value) 0.77 0.79 0.72 0.65 0.62 Transverse crystal structure (POM) whole Clear and complete part part Not obvious Processing fluidity Acceptable good Difference Good (but with frizzy edges) good Appearance defects none none none none none

[0173] Referring to Table 5, Examples 7 and 8 used highly crystalline homopolymer polypropylene, with flexural modulus above 2480 MPa; impact strength (23℃) above 5.7 kJ / m²; heat distortion temperature above 129℃; β crystal content above 0.77; and complete or clear transverse crystal structure observed under a polarizing microscope.

[0174] Comparative Example 12 suffered from poor processing fluidity and difficulty in mold filling due to its excessively low melt flow rate, resulting in uneven dispersion of the attapulgite clay, a flexural modulus of only 2180 MPa, a heat distortion temperature of only 126℃, and an incomplete transverse crystal structure. Comparative Example 13 suffered from insufficient matrix strength due to its low PP molecular weight, resulting in a flexural modulus of only 2010 MPa, an impact strength of only 4.5 kJ / m², and a heat distortion temperature of only 118℃. Comparative Example 14, although having a melt flow rate within the preferred range, suffered from low crystallinity, insensitivity to nucleating agents, a β-crystal content of only 0.62%, and an indistinct transverse crystal structure, resulting in a flexural modulus of only 2250 MPa and an impact strength of only 4.8 kJ / m².

[0175] The results show that when the melt flow rate of highly crystalline homopolymer polypropylene is 5–15 g / 10 min, it can ensure the processing compatibility and nucleation sensitivity with modified attapulgite, thereby obtaining an ideal transverse crystal structure and excellent comprehensive performance.

[0176] Comparative Example 15

[0177] In this embodiment, the nucleating agent is changed to α-nucleating agent Millad 3988, based on Comparative Example 1.

[0178] Comparative Example 16

[0179] In this embodiment, the nucleating agent is changed to rare earth β-nucleating agent WBG-1, based on Comparative Example 1.

[0180] The detection performance of Comparative Example 15 and Comparative Example 16 is shown in Table 6.

[0181] Table 6:

[0182] Components / Performance Comparative Example 14 Comparative Example 15 Flexural modulus (MPa) 2720 2350 Impact strength (kJ / m², 23℃) 3.8 5.4 Heat distortion temperature (°C) 128 128 β crystal content (K value) 0.06 0.61 Transverse crystal structure (POM) Partial (α crystal) whole

[0183] Referring to Table 6, although Comparative Example 14 has the highest flexural modulus (2720 MPa), its β-crystal content is extremely low, resulting in an impact strength of only 3.8 kJ / m², indicating an imbalance between stiffness and toughness. Comparative Example 15 has a low grafting rate and a β-crystal content of 0.61, making its overall performance lower than that of Example 1.

[0184] Performance testing methods

[0185] The granules prepared in each embodiment and comparative example were injection molded into standard test strips for the following performance tests:

[0186] (1) Bending modulus test: According to ISO 178-2010 standard, the sample size is 80×10×4 mm, the test speed is 2 mm / min, and the span is 64 mm.

[0187] (2) Cantilever beam notched impact strength test: According to ISO 180 / 1eA-2010 standard, the sample size is 80×10×4mm, with type A notch, pendulum energy is 2.75 J, and the test temperature is 23℃ and -30℃.

[0188] (3) Heat distortion temperature test: According to ISO 75-2-2013 standard, the sample size is 80×10×4 mm, the sample is placed flat and loaded with a load of 0.45 MPa and a heating rate of 120℃ / h.

[0189] (4) Determination of the relative content (K value) of β crystals: A wide-angle X-ray diffractometer (XRD) was used with Cu Kα rays (λ=0.15418nm), tube voltage 40 kV, tube current 40 mA, scanning range 2θ=5°~35°, and scanning rate 2° / min. The relative content of β crystals was calculated according to the Turner-Jones formula.

[0190] (5) Observation of transverse crystal structure under polarized light microscope: Place the ultrathin section of the sample (thickness 5-10 μm) under an orthogonal polarized light microscope to observe the crystal morphology.

[0191] (6) Scanning electron microscopy cross-section observation: After the brittle fracture surface of the impact sample is treated with gold spraying, the dispersion state and interface bonding of the attapulgite soil are observed under a scanning electron microscope.

[0192] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.

Claims

1. A lightweight, high-strength plastic material, characterized in that, include: Polypropylene resin and modified attapulgite; for every 100 parts by weight of polypropylene resin, the amount of modified attapulgite is 2 to 10 parts. The modified attapulgite is attapulgite rod crystals with end-selective grafting nucleating agents.

2. The lightweight, high-strength plastic material according to claim 1, characterized in that, The length of the attapulgite rod crystals is 1 to 3 μm, and the aspect ratio is not less than 20:

1.

3. The lightweight, high-strength plastic material according to claim 1, characterized in that, The cation exchange capacity of the attapulgite rod crystals does not exceed 30 meq / 100g, and the specific surface area is 150-210 m² / g.

4. The lightweight, high-strength plastic material according to claim 1, characterized in that, The degree of dissociation of the rod-shaped crystal bundles of the attapulgite is not less than 90%.

5. The lightweight, high-strength plastic material according to claim 1, characterized in that, The polypropylene resin is a highly crystalline homopolymer polypropylene with a melt index of 5–15 g / 10 min.

6. The lightweight, high-strength plastic material according to claim 1, characterized in that, The nucleating agent is an aromatic amide β-nucleating agent.

7. A method for preparing a lightweight, high-strength plastic material, characterized in that, include: Activated attapulgite is obtained by purifying and activating the end groups of attapulgite rod crystals. The activated attapulgite was dispersed in a solvent, a coupling agent was added, and the mixture was refluxed at 100–110°C for 4–6 hours under nitrogen protection. After washing and drying, the coupling agent-modified attapulgite was obtained. The coupling agent-modified attapulgite, nucleating agent, and condensing agent are added to a solvent to carry out a grafting reaction, and the reaction product is extracted and purified by a Soxhlet extractor to obtain modified attapulgite. The modified attapulgite clay and polypropylene resin are mixed in a certain proportion, and then melt-blended and extruded granulated using a twin-screw extruder to obtain a lightweight, high-strength plastic material.

8. The method for preparing a lightweight, high-strength plastic material according to claim 7, characterized in that, The purification process includes: preparing attapulgite rod crystals into an aqueous suspension, and then subjecting them to high-speed stirring, static sedimentation, centrifugation, drying, and sieving to obtain purified attapulgite rod crystals. The end-group activation treatment includes: adding purified attapulgite rod crystals to a 0.5-2.0M hydrochloric acid solution, refluxing at 60-90°C for 1-4 hours, washing until neutral and drying to obtain activated attapulgite.

9. The method for preparing a lightweight, high-strength plastic material according to claim 7, characterized in that, Before adding the coupling agent-modified attapulgite, nucleating agent, and condensing agent to the solvent for grafting reaction, the method further includes: subjecting the activated attapulgite to flow field-assisted dispersion treatment, wherein the flow field-assisted dispersion treatment is ultrasonic dispersion treatment for 20 to 60 min under the conditions of frequency 20 to 40 kHz and power density 50 to 200 W / L.

Citation Information

Patent Citations

  • Low-odor reinforced polypropylene composite material and preparation method thereof

    CN121758862A

  • Polypropylene composition as well as preparation method and application thereof

    CN122127697A